Tutors’ Creativity in Enhancing the Motivation and Enthusiasm of Learners at PKBM Ar Royan, Pekanbaru - Nur Azica Sardi; Nur Paziah; Anggala Regina; Rika Fitri Ramadhani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study is motivated by the low enthusiasm and engagement of learners at PKBM Ar Royan Pekanbaru, characterized by limited active participation, poor attendance, and minimal involvement in learning activities. These conditions stem from monotonous teaching methods, limited learning media, and the diverse social and educational backgrounds of the learners. Therefore, tutor creativity in designing and implementing varied, innovative, and contextual learning activities is essential to address these challenges. This study aims to describe and analyze the forms of tutor creativity and their impact on increasing the enthusiasm and engagement of learners at PKBM Ar Royan Pekanbaru. The creativity examined includes the use of varied teaching methods (combining lectures, group discussions, simulations, question-and-answer sessions, and educational games), innovative learning media (videos, pictures, and simple props based on daily life contexts), and a personal approach tailored to individual learners' characteristics and needs. This research uses a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation. The results indicate that consistently applied tutor creativity significantly improves learner enthusiasm and engagement, as evidenced by increased attendance, active participation, and emotional involvement in the learning process.